2016
DOI: 10.1016/j.jphotobiol.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

A novel Schiff base derived from the gabapentin drug and copper (II) complex: Synthesis, characterization, interaction with DNA/protein and cytotoxic activity

Abstract: A novel Schiff base [C20H23NO3], has been prepared and characterized using FT-IR, UV-vis, (1)H NMR spectroscopy, elemental analysis and X-ray crystallography. A copper (II) complex [Cu(C20H22NO3)2]·H2O has also been synthesized and characterized. The new ligand and complex thus obtained were investigated by their interaction with calf thymus DNA and BSA using electronic absorption spectroscopy, fluorescence spectroscopy, and thermal denaturation. The intrinsic binding constants Kb of the ligand and Cu (II) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 85 publications
0
44
0
Order By: Relevance
“…The complex was investigated for its interaction with calf thymus DNA and bovine serum albumin using spectroscopic methods. The results revealed that the binding mechanism is a static quenching process 57. The in vitro cytotoxic evaluation study was conducted using MTT assay, and the result revealed that a copper complex exhibited enhanced cytotoxicity, high selectivity and dose-dependent cytotoxicity 57…”
Section: Anticancer Properties Of Copper Complexesmentioning
confidence: 99%
“…The complex was investigated for its interaction with calf thymus DNA and bovine serum albumin using spectroscopic methods. The results revealed that the binding mechanism is a static quenching process 57. The in vitro cytotoxic evaluation study was conducted using MTT assay, and the result revealed that a copper complex exhibited enhanced cytotoxicity, high selectivity and dose-dependent cytotoxicity 57…”
Section: Anticancer Properties Of Copper Complexesmentioning
confidence: 99%
“…Investigated results showed that copper complex (Fig. 4) show positive synergic effect and high selective in dose dependent manner [13].…”
Section: Introductionmentioning
confidence: 96%
“…New Schiff base ligand with molecular formula (C 20 H 23 NO 3 ), has been prepared and treated with copper metal [13]. The copper metal complex was screened for spectroscopic analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of ligands and complexes ( 1 ) and ( 2 ) with DNA has been recorded by the use of MB. MB is a well‐known intercalator and tricyclic that is often used as a spectral probe to establish the mode of binding of small molecules to double‐helical DNA. The emission spectra of the MB‐DNA solution are shown in Figure by the addition of various amounts of ligands and complexes ( 1 ) and ( 2 ).…”
Section: Resultsmentioning
confidence: 99%